2016
DOI: 10.4314/mejs.v8i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Magnitude of Sexually Transmitted Infections, Sexual and Reproductive Health Status among Prisoners Aged Between 18-49 Years in Tabor Prison, Hawassa, Ethiopia

Abstract: Lack of access to SRH is a major public health concern, especially in developing countries. The objective of the study is to assess the magnitude of STIs and SRH status among prisoners aged between 18-49 years in Tabor prison, Hawassa, Ethiopia. A descriptive cross sectional study was conducted. Systemic random sampling technique was used and the sample size was 292. The living status of the respondents before detention ( 2 =12.8, p<0.05), maternal and paternal education ( 2 =20.6, p<0.05), and sexual health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 3 publications
(3 reference statements)
1
18
1
Order By: Relevance
“…In the current study, age, gender, marital status, duration in a prison, history of sharing shaving materials or dental extraction were not significantly associated with HIV seropositivity. This finding was similar with previously reported studies [5,11]. However, study participants with body tattoo on any part of their bodies were 9.3 times more likely to be HIV infected.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the current study, age, gender, marital status, duration in a prison, history of sharing shaving materials or dental extraction were not significantly associated with HIV seropositivity. This finding was similar with previously reported studies [5,11]. However, study participants with body tattoo on any part of their bodies were 9.3 times more likely to be HIV infected.…”
Section: Discussionsupporting
confidence: 92%
“…In the present study the rate of HIV infection detected was 2.6%, which is lower than previously reported rate among prisoners (6.0%) [5]. This difference might be due to the factors associated with the transmission of HIV infection in a closed prison, which put prisoners at high risk for HIV infection, like lack of condom availability or their social misbehavior before coming to prison which is different from one area to the other [3].…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…In total, 23 studies, reported alcohol or illicit drugs abuse in their study population. 3 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 26 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 39 , 41 , 42 , 50 In regard to alcohol, nine studies reported different rates of alcohol consumption among their incarcerated participants with rates ranging from 20.7% to 81.8%. 14 , 16 , 19 , 23 , 26 , 27 , 29 , 34 , 42 In addition, 22 studies indicated illicit drug abuse in their study population ranging from 6.3% to 78.3%, 3 , 14 , 15 , 16 , 17 , 19 , 20 , 21 , 23 , 25 , 27 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , …”
Section: Discussionmentioning
confidence: 99%
“…Among these studies, three cross‐sectional studies and one RCT only used clinical questionnaires and sign and symptoms self‐reports to assess the prevalence of STDs in their inmate population. 19 , 21 , 26 , 44 While the remaining 28 studies utilized at least one laboratory diagnostic test or more to confirm and evaluate the STIs among their participants. Among these studies, four mentioned only “blood sample” in their published full‐text article and did not note the specific diagnostic test used.…”
Section: Discussionmentioning
confidence: 99%